Fostering Growth for Golden Indonesia 2045 through Stunting Prevention Training and MPASI Making Education - Safitri, Ani; Rahmawanti, Movi Riana; Fatonah, Umi; Hadiyual, Afifah (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
Abstract: Stunting prevention is crucial for realizing Golden Indonesia 2045. By addressing stunting, we improve human capital, boost productivity, and ensure sustainable development, paving the way for a prosperous and globally competitive Indonesia in 2045. This research investigates women’s beliefs about weaning foods as a means of preventing stunting, as well as the actions to take to avoid it. In addition, some challenges in preventing stunting were also investigated. Under a descriptive qualitative study design, observations, interviews, and a questionnaire were administered to participants. The participants were mothers and pregnant women. The research took place at one of the care centers for prenatal and postnatal care in Bogor Regency, called Posyandu Mawar 03, Dukuh Village. Once the data were collected, they were analyzed using thematic analysis. Findings showed that participants had some misunderstandings about weaning food and that training could help close the gap in understanding. It is also found that the training itself has some drawbacks and challenges. Keywords: care center for pre- and postnatal, stunting, training, weaning food (MPASI)